Gestão por competências nos cursos de Arquivologia no Brasil: abordagem nos princípios da Gestão do Conhecimento - Casimiro, Adelaide Helena Targino (2019)
The studies that are based on the principles of Knowledge Management (KM) have their bases linked to the creation of environments favorable to the controlled sharing of the knowledge of each individual. This dissertation had the objective to analyze the practice of Management by Competences (MbC) applied to Graduation Degree in Archivology at the national level. The four specific objectives are to recognize the compulsory subjects that form the common axis between universities; to point out the competences required for the course through common compulsory subjects; to map the technical-professional competences of the teachers who teach the common compulsory subjects to the courses; and to compare the essential competences of the courses with the essential individual skills of the teachers. As far as the methodology is considered of direct documentary nature because uses primary sources, the method is inductive, whereas the objectives are exploratory and descriptive, applying the qualitative and quantitative-decritive approach. As for the procedures were used the statistical and typological, since the dependent and independent variables are the categories and Lattes résumé of the teachers respectively. The research universe used is the common compulsory subjects of the 16 universities that have Graduation Degrees in Archivology authorized by the Brazilian Ministry of Education and the teachers who work in their respective disciplines. Lattes résumé were analyzed according to the Content Analysis method, with the Management by Competences guidelines and descriptive statistics techniques. The results indicate that there are indications of the application of Management by Competences in the common compulsory subjects of Graduation Degrees in Archivology in Brazil. The analyzes and discussions developed allow us to conclude that the hypothesis raised, that the teachers of Graduation Degrees in Archivology are allocated in the disciplines according to their technical-professional competences, is partially true and corresponds to half of the categories of common compulsory subjects. While the other half do not have equally positive rates. If MbC is employed in an adequate, efficient and effective way, it can heal or minimize the problems pointed out and increase the indexes found during this research, besides adding numerous benefits to the public service. It is hoped that with this work, the MbC can be considered as an emergent solution to the questions that are presented in said courses.